Begging behavior as an honest signal of need and parent–offspring association during the postfledging dependency period. Issue 13 (17th June 2019) - Davis, Kayla L.; Karpanty, Sarah M.; Spendelow, Jeffrey A.; Cohen, Jonathan B.; Althouse, Melissa A.; Parsons, Katharine C.; Luttazi, Cristin F.
Abstract: Honest signaling mechanisms can function to appropriate care to hungry offspring and avoid misdirected care of unrelated offspring. Begging, the behavior by which offspring solicit food and parental care, may be an honest signaling mechanism for need, as well as association of parents and offspring. Roseate terns ( Sterna dougallii ) exhibit prolonged parental care during the postbreeding staging period, offering an ideal system in which to study begging as an honest signaling mechanism. We conducted focal sampling during two premigratory staging seasons (2014 and 2015) at Cape Cod National Seashore, Massachusetts, USA to determine whether postfledging tern begging behavior was an honest signal for need and parent–offspring association. Based on honest signaling theory, we expected begging behavior to be highest during times of high perceived need, and we expected to see a decrease in begging behavior as young terns became increasingly independent of the care‐giving parent. Also, we predicted that young terns would be more likely to beg at parents than nonparents. We found that young roseate terns begged at their parents more often than nonparents; however, they did not always beg at parents. Model predictions of begging probability showed a linear relationship between begging and time of day and date of season, such that begging increased with time of day and decreased with date of season, respectively. Our results provide evidence for honest parent–offspring interactions and are inconsistent with parent–offspring conflict theory but suggest that begging may play a complex role in postfledging parent–offspring interactions. OPEN RESEARCH BADGES: This article has been awarded Open Data, Open materials Badges. All materials and data are publicly accessible via the Open Science Framework athttps://doi.org/10.5281/zenodo.2656718 . Abstract : In our study of hatch‐year roseate tern begging behavior during the postbreeding staging period, we observed decreases in tern begging frequency as the staging season progressed. However, young terns continued to beg at parents even at the end of the staging season. This could indicate the existence of a soft independence period or a prolonged parent–offspring bond poststaging. Our results are inconsistent with parent–offspring conflict theory and suggest that begging plays a complex role in postfledging parent–offspring dynamics.